Perubahan Sosial, Pendidikan, dan Mobilitas Sosial: Studi Kasus Mahasiswa Perguruan Tinggi di Mataram - Habib, Abdul; Ningsih, Dewi Puspita; Apriawan, Andika (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Higher education is often regarded as a crucial instrument in fostering social change and upward mobility in Indonesia. This study examines the interrelation between education, social mobility, and social transformation, with a particular focus on university students in Mataram City. The research combines literature review with secondary data obtained from the Central Bureau of Statistics and the Higher Education Database. Findings reveal that higher education in Mataram serves not only as a medium for improving economic status but also as a vehicle for socio-cultural transformation. The relatively high proportion of the population with tertiary education in Mataram (12.76% as of 2024) underscores the pivotal role of education as a determinant of social mobility. However, a paradox emerges when access to education has not fully succeeded in eliminating social disparities, especially among vulnerable groups. This study highlights the strategic role of higher education in strengthening intergenerational mobility, while at the same time identifying challenges rooted in structural inequalities and complex social dynamics among students.